Family Allowance and Pension Dependent on the Number of Children: Optimality and Neutrality: Reaction to „The Inherent Faults of the State Pension System and the Main Direction of its Improvement” by József Banyár - Simonovits, András (Public Finance Quarterly, 2020)
When it comes to the neutralisation of child-rearing burdens by the state, many experts support the introduction of pensions dependent on the number of children (or dependent on child-rearing) instead of family allowance (and tax allowance) (cf. Kovács ed., 2012). The critical review by Banyár (2019) joins this trend. Leaving external criticism aside, I assess Banyár’s plan of reduced pension of childless people and the remaining family allowance in the simplest possible optimisation model. The relative child consumption plays a key role. My main findings: a) in case of a critical relative value (when the total child consumption of the family equals the parents’ consumption), both pension of the childless and family allowance are dispensable; b) in case of a lower child relative value, the reduced pension of the childless is positive, and family allowance is dispensable; c) in case of a higher relative value, the pension of the childless is zero, but family allowance is indispensable.